Telehealth Inequity and Youth Engagement: A Mixed Methods Study of Access, Literacy, and Culture - Bahrianoor; Febriana, Ajeng Iva Dwi (Communica : Journal of Communication, 2024)
Telemedicine is increasingly promoted to reduce healthcare disparities in rural regions, yet rural youth remain underserved by digital health innovations. This mixed methods study combined national survey data from Hungary and Sub-Saharan Africa (n = 3,240 adolescents) with 46 in-depth interviews and 12 focus groups in Southeast Asia to examine infrastructural, educational, economic, and cultural barriers to telemedicine adoption. Results showed that fewer than 50% of rural households in Sub-Saharan Africa had stable electricity and only 24% reported internet access, compared to 88% and 62% respectively in rural Hungary. Device ownership was also limited, with just 18% of rural Sub-Saharan youth owning smartphones. Digital health literacy scores were significantly lower among rural adolescents, while cultural preferences for traditional medicine and skepticism toward digital platforms further reduced uptake. Economic constraints, particularly the cost of mobile data, posed additional barriers. Ethical issues around privacy and consent were critical, especially for minors. These findings highlight the need for affordable infrastructure expansion, school-based digital literacy programs, and culturally sensitive outreach. The study concludes that telemedicine can transform rural healthcare access if implemented through equitable infrastructure investment, inclusive education, and participatory, youth-centered policy design.